Ileocaecal Intussusception with a Lead Point: Unusual MDCT Findings of Active Crohn’s Disease Involving the Appendix - Ebru Ozan; Gokce Kaan Atac; Egemen Akincioglu; Mete Keskin; Kamil Gulpinar (Case Reports in Radiology)
Adult intussusception is a rare entity accounting for 1% of all bowel obstructions. Unlike intussusceptions in children, which are idiopathic in 90% of cases, adult intussusceptions have an identifiable cause (lead point) in the majority of cases. Crohn’s disease (CD) may affect any part of the gastrointestinal tract, including the appendix. It was shown to be a predisposing factor for intussusception. Here, we report a rare case of adult intussusception with a lead point, emphasizing diagnostic input of multidetector computed tomography (MDCT) in a patient with active CD that involves the appendix.